Analisis Hambatan dalam Kemampuan Membaca Siswa Kelas Tinggi di SDN Pacarkembang 1/192 - Ainia, Carryna Zalfa; Wahyudi, Adisti Istivari; Febrianto, Priyono Tri; Saropah, Siti (ARZUSIN, 2025)
This study is motivated by the limited research on reading difficulties among elementary school students, despite the fact that such issues significantly impact academic achievement and literacy development. The aim of this study is to analyze the various obstacles affecting the reading ability of fifth-grade students at SDN Pacarkembang 1/192. A descriptive qualitative approach was used, with a sample consisting of the principal, classroom teacher, and students selected through purposive sampling based on their direct involvement in the learning process. Data were collected through observation, interviews, and documentation, and analyzed thematically. The results reveal that students’ reading difficulties include low reading interest, slow reading speed, difficulty identifying main ideas and key information, and trouble maintaining focus when reading long texts. Contributing factors are categorized into internal factors, such as lack of reading awareness and low learning motivation, and external factors, such as limited family support and the absence of a literacy culture at home. These findings emphasize the importance of the environment in literacy development and support theories that view literacy as a product of individual interaction with social context. The main conclusion of this study is that reading comprehension ability is influenced by a combination of individual and social environmental factors. The implications include theoretical contributions to the literature on basic literacy and practical recommendations for teachers to adopt more engaging instructional strategies, and for parents to create a home environment that supports reading activities. This study also opens opportunities for further research on effective interventions to increase students’ reading interest and habits.